Pemetaan Tingkat Kebisingan Dari Kegiatan Transportasi Di Jalan Jenderal Sudirman Kota Pekanbaru - Sasmita, Aryo; Andesgur, Ivnanaini; Lestari, Rika (Jurnal Teknik Sipil, 2025)
High vehicle volume will produce noise that causes health problems, lack of rest and sleep, lack of thinking ability, and communication disorders. The purpose of this study was to obtain noise level patterns on the main road of Pekanbaru City, namely Jalan Jenderal Sudirman. A preliminary survey was conducted to determine the time of the study. The Sound Level Meter (SLM Lutron LM-8102) was used to conduct this study and the noise mapping method for two days, on Monday, which shows peak hours, and Saturday shows off hours of vehicles. Data were collected from 180 points for noise measurement. Other data collected were air humidity, air temperature, and wind speed. According to the results of the study, the highest noise level was 97.9 dB which is a point with high traffic volume, and the lowest noise level was 68.4 dB which has low traffic volume.